2011
DOI: 10.1016/j.jcf.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an antioxidant-rich multivitamin supplement in cystic fibrosis

Abstract: In this study, AquADEKs® increased systemic antioxidant levels, while maintaining vitamin A levels in the normal range, and improved but did not completely normalize vitamin D and K status. Increased β-carotene levels were associated with improved growth parameters. These results warrant further clinical evaluation in CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 36 publications
3
24
1
1
Order By: Relevance
“…AquADEKs ® by Yasoo Health, Inc. is a vitamin supplement specifically formulated to meet the antioxidant needs of those with CF, and is commercially available. It has been shown to improve lung function, normalize vitamin levels in plasma and reduce neutrophilic inflammation (Sagel et al, 2011).…”
Section: Current Cf Therapiesmentioning
confidence: 99%
“…AquADEKs ® by Yasoo Health, Inc. is a vitamin supplement specifically formulated to meet the antioxidant needs of those with CF, and is commercially available. It has been shown to improve lung function, normalize vitamin levels in plasma and reduce neutrophilic inflammation (Sagel et al, 2011).…”
Section: Current Cf Therapiesmentioning
confidence: 99%
“…In fact, based in large measure on the results of the experimental animal studies mentioned above, a clinical trial of combined cholesterol-antioxidant therapy for SLOS is currently underway at Children’s Hospital Colorado.The initial results appear promising [23] based upon electroretinographic (ERG) testing outcomes, significant improvement in retinal function has been achieved by treating children affected with SLOS with cholesterol supplementation augmented with AquADEKs ® , a multivitamin and mineral formulation that includes several antioxidants and micronutrients, including vitamins A, D, E, and K. AquADEKs ® has been used previously for treatment of cystic fibrosis patients [24,25], but has been “repurposed” for off-label use in this SLOS treatment trial.…”
mentioning
confidence: 99%
“…The increase in antioxidant vitamin serum levels occurred with respect to the other liposoluble vitamins (D and K). Respiratory function barely improved, and the negligible reduction in urinary 8-isoprostanes meant any impact of this supplementation on OxS was unlikely (134,161). Some authors also reported that a resistance to oxidation correlated with a-tocopherol levels in low-density lipoprotein and a reduction in malondialdehyde (156) ( Table 2).…”
Section: Antioxidantsmentioning
confidence: 99%